Nonlinear dynamic and vibration analysis of piezoelectric eccentrically stiffened FGM plates in thermal environment. (September 2016) - Duc, Nguyen Dinh; Cong, Pham Hong; Quang, Vu Dinh
Abstract: In this paper, the nonlinear dynamic response and vibration of a plate made of piezoelectric functionally graded materials (FGM) and reinforced by eccentrically outside stiffeners with piezoelectric actuators resting on Pasternak type elastic foundations subjected to mechanical and electrical loads in thermal environment are investigated. One of the salient features of this work is the consideration of temperature on the piezoelectric layer, stiffeners and all of them (the plate, outside stiffeners, piezoelectric layers) are deformed under temperature. The material properties of the FGM plates are assumed to be temperature dependent. The governing equations for the plates are derived by using the first order shear deformation theory of plates, taking into account both the geometrical nonlinearity in the von Karman sense, initial geometrical imperfections and different types of boundary conditions. The effects of geometrical parameters; material properties; imperfections; elastic foundations; stiffeners and thermal stress in stiffeners; mechanical and electrical loads, temperature on the nonlinear dynamic response and vibration of the piezoelectric FGM plates are studied simultaneously for first time. Highlights: The nonlinear dynamic response and vibration of the piezoelectric FGM plates. The plate reinforced by eccentrically stiffeners on elastic foundations. The plate subjected to mechanical and electrical loads in thermal environment. The plate, stiffeners, piezoelectric layers are deformed under temperature. The first order shear deformation theory of plates was used.